PEMBANGUNAN STANDARD PENGUKURAN KEMAHIRAN ‘EMPLOYABILITY’ (Sains Humanika, 2008)
Mastering employability skills is one of the global problems which employers are facing with graduates or their future employees. Many kind of research in this employability skills have been conducted nationally and internationally and it was found that many technical graduates nowadays are lacking in employability skills rather than technical skills. The aim of this study is to develop a standard measurement of employability skills that can be used by employers, lecturers and individuals to measure, evaluate and monitor the employability skills. Samples for the research consist of 107 employers from manufacturing industry. Inputs from employers are used to identify aspects of the employability skills that is important to employers in the manufacturing industry. Ranking of the aspects which is used as items in the development of the standard. Method used in developing this skill employability standard is the Kepner–Tregoe Method, in which a weight factor is set.
Keywords: Employability skill; employability skill assessment standard; weight factor; decision making analysis